Functional Characterization of the GH10 and GH11 Xylanases from Streptomyces olivaceoviridis E-86 Provide Insights into the Advantage of GH11 Xylanase in Catalyzing Biomass Degradation - Yagi, Haruka (J Appl Glycosci (1999), 2019)
We functionally characterized the GH10 xylanase (SoXyn10A) and the GH11 xylanase (SoXyn11B) derived from the actinomycete Streptomyces olivaceoviridis E-86. Each enzyme exhibited differences in the produced reducing power upon degradation of xylan substrates. SoXyn10A produced higher reducing power than SoXyn11B. Gel filtration of the hydrolysates generated by both enzymes revealed that the original substrate was completely decomposed. Enzyme mixtures of SoXyn10A and SoXyn11B produced the same level of reducing power as SoXyn10A alone. These observations were in good agreement with the composition of the hydrolysis products. The hydrolysis products derived from the incubation of soluble birchwood xylan with a mixture of SoXyn10A and SoXyn11B produced the same products as SoXyn10A alone with similar compositions. Furthermore, the addition of SoXyn10A following SoXyn11B-mediated digestion of xylan produced the same products as SoXyn10A alone with similar compositions. Thus, it was hypothesized that SoXyn10A could degrade xylans to a smaller size than SoXyn11B. In contrast to the soluble xylans as the substrate, the produced reducing power generated by both enzymes was not significantly different when pretreated milled bagasses were used as substrates. Quantification of the pentose content in the milled bagasse residues after the enzyme digestions revealed that SoXyn11B hydrolyzed xylans in pretreated milled bagasses much more efficiently than SoXyn10A. These data suggested that the GH10 xylanases can degrade soluble xylans smaller than the GH11 xylanases. However, the GH11 xylanases may be more efficient at catalyzing xylan degradation in natural environments (e.g. biomass) where xylans interact with celluloses and lignins.